From Forgotten Works - to Staging as Form - Winkelhorn, Kathrine; Mølle Lindelof, Anja (Peripeti, 2017)
This chapter examines Hotel Pro Forma’s staging of Rachmaninov’s Troika: three operas. Aleko, The Miserly Knight and Francesca da Rimini produced at the Belgian opera, La Monnaie and shown at the National Theatre in Brussels.